Visual Precedence As a Subject of Linguistic Research: Current State and Development Prospects - L. A. Mardieva (Ученые записки Казанского университета: Серия Гуманитарные науки, 2023)
This article reviews the published studies on visual precedence (pre-existing visual phenomena), which is a relatively new subject of linguistic research. It is shown that the active growth of the conceptual and terminological system related to visual precedence is accompanied by terminological ambiguities in defining pre-existing visual phenomena, by a lack of unanimity and contradictory reasoning about their forms in textual structures, as well as by an expanding range of phenomena attributed to visual precedence. At the beginning of the second decade of the 21st century, the specifics of pragmatic predetermination and use of the analyzed forms of pre-existing visual phenomena in political and media discourses have been highlighted. Furthermore, representative data have been collected on their origins and transfer into advertising discourse, and the first steps have been taken to better understand how these phenomena are used in other types of discourse, such as literary, artistic, popular science, educational, and portrait imagery. Researchers have distinguished between the general and particular (characteristic of specific communication domains) functions of pre-existing visual phenomena, and some progress has also been made in studying certain technologies actualizing their pragmatic functions. Based on their functional-pragmatic well-formedness, pre-existing visual phenomena can be considered as visual stylistic means, indicating the emergence of visual stylistics of the text.